(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
This article describes and analyzes some links between the concepts of arbitrary reinforcers, natural reinforcers, immediate – or short-term reinforcers and long term reinforcers found in the literature, concerning its specific use in the design of cultural practices. Texts were selected reading the titles, abstracts and keywords. After selection, the texts were classified, as referring to the relationship between reinforcers. Twenty eight texts were selected, of which 18 were classified as texts with reference to the links. If was considered that, although the major publications of Behavior Analysis revealed that these principles have been consistently studied in basic research, only recently, due to the expansion of projects and interventions related to cultural analysis and planning, became important to explore vertically some of its main theoretical and practical implications.